One-pot synthesis of SnO2 nanoparticles and SnO2@rGO nanocomposite by laser pyrolysis and its application in Li-ion batteries - To, Phung Huy (2016)
Laser pyrolysis has be employed many times previously as an affordable method to synthesize small size nanoparticles. In this study, we report for the first time the use of laser pyrolysis to create SnO2 nanoparticles and SnO2@rGO nanocomposite via a one-pot synthesis method. SnO2 was used due to its high theoretical capacity coming mostly from both conversion and alloying reaction. The resulting materials were characterized via SEM, XRD, XPS and TGA, which reveals very low level of impurities and particle dimensions of mostly 15nm or less. The materials were also tested for electrochemical performance via cyclic voltammetry, galvanic charge/discharge and rate cycling at different current densities. The results portray great storage capacity of the materials, especially the nanocomposite, at both low and high current rate. For SnO2@rGO, charge capacity can reach as high as 1650 mAh g-1 at 100 mA g-1 and 1370 mAh g-1 at 2000 mA g-1. The material also showed great rate capability with capacity still remain as high as 988 mAh g-1 at extremely high current rate of 10A g-1. However, it was also noted that capacity retention during cycling is only satisfactory as capacity drop of as high as 23% has been observed after only 50 cycles of charge/discharge. The entire investigation can be deemed a success as it has demonstrated that one-pot laser pyrolysis are able to synthesize nanoparticles and metal oxide/graphene nanocomposite with decent electrochemical properties.